The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1159/000335077
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Short- and Long-Term Hypercholesterolemia on Contrast-Induced Acute Kidney Injury

Abstract: Background: Whether hypercholesterolemia is a risk factor for contrast-induced acute kidney injury (CI-AKI) remains unclear. In the present study, the effects of short- and long-term dietary hypercholesterolemia on contrast media-induced nephrotoxicity were evaluated. Methods: Rats were fed either a normal rodent diet (N) or high-cholesterol diet (H). At the end of 2 and 8 weeks, 8 rats from each diet group were given a tail vein injection of either iohexol (group NC and group HC) or vehicle (group N and group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 37 publications
(26 reference statements)
2
24
0
Order By: Relevance
“…Recently, Yang et al found that CM administration increased serum creatinine levels and induced severe renal tubular necrosis in rats fed the high-cholesterol diet for 8 weeks but not in rats fed the normal diet or high-cholesterol diet for 2 weeks. 9 Our study also found that in CM-injected rats with hypercholesterolemia vacuolar degeneration of tubular epithelial cells, tubular dilation, protein cast, loss of tubular brush border, and increased epithelial cell shedding were observed. These studies demonstrated that hypercholesterolemia was an important risk factor for radiocontrast nephrotoxicity.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Recently, Yang et al found that CM administration increased serum creatinine levels and induced severe renal tubular necrosis in rats fed the high-cholesterol diet for 8 weeks but not in rats fed the normal diet or high-cholesterol diet for 2 weeks. 9 Our study also found that in CM-injected rats with hypercholesterolemia vacuolar degeneration of tubular epithelial cells, tubular dilation, protein cast, loss of tubular brush border, and increased epithelial cell shedding were observed. These studies demonstrated that hypercholesterolemia was an important risk factor for radiocontrast nephrotoxicity.…”
Section: Discussionsupporting
confidence: 76%
“…The rats were randomly divided into normal diet group (NN, n ¼ 8) and high cholesterol supplemented dietary group (HN, 4% cholesterol and 1% cholic acid, n ¼ 32). 9 At the end of 8 weeks, 1 rat given normal diet died and 4 rats given high cholesterol supplemented dietary died, then the rats with high cholesterol diet were randomly divided into four subgroups (7/group): high cholesterol diet group (HN), high cholesterol plus diatrizoate group (HH), high cholesterol plus diatrizoate plus MTP131 group (HM), and high cholesterol plus diatrizoate plus SPI20 group (HS). All experiments were approved by the Medical Science Animal Care Committee of the Central South University.…”
Section: Reagents and Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The elevated urea level in hypercholesterolemic rats is likely due to increased amino acid catabolism, impaired kidney function or liver damage (Pedraza et al, 2004). Yang et al (2012) observed an increased serum creatinine levels and induced severe renal tubular necrosis in rats fed the high-cholesterol diet for 8 weeks but not in rats fed the normal diet or high-cholesterol diet for 2 weeks. The authors concluded that long-term hypercholesterolemia appeared to be a risk factor for contrast-induced acute kidney injury (CI-AKI), which might be associated with disorders in intrarenal prostaglandins and abnormalities in renal nitric oxide system induced by lipid peroxidation.…”
Section: Discussionmentioning
confidence: 83%
“…[21][22][23] However, the findings of most of the studies are inconsistent, except for the positive effect of hydration or hydration in combination with N-acetylcysteine (NAC) or sodium bicarbonate before the procedure. 24 Recently, Onbaşılı et al were the first to report that TMZ-a cellular anti-ischemic agent-was effective in preventing CIN in patients undergoing coronary procedures.…”
Section: Discussionmentioning
confidence: 99%